ROMANIAN RURAL ENTREPRENEURS RESPONSE TO SUPPORT MEASURES FROM CAP SECOND PILLAR - Turtoi, Crina; Toma, Camelia; Gavrilescu, Camelia (Economics of Agriculture, 2011)
Romanian rural areas are to cope with the dynamics of radical change, dismantling and restructuring of agricultural structures and processes. The reform of the Common Agricultural Policy, directly concerned with rural value added, employment and environmental degradation, had generated a two-strand approach in implementing agricultural policy. Entrepreneurship, innovation, learning, adoption and evolving institutional frameworks are integral parts to this process. Dealing with the vision of a cleaner, more productive and effcient agriculture, by its supporting measures Common Agricultural Policy is strengthening the position of the farming community by encouraging the rural entrepreneurship and setting up the young farmers in rural space. The results of the study argued in favor of considering the priorities of the supporting measures under the two main components of the CAP second pillar: the sectorial function, specifc to agricultural policy reform, and the territorial function specifc for the rural economy and population.